Unsur Intrinsik dalam Analisis Bandingan Cerita Rakyat Asal-Usul Danau Toba dengan Cerita Rakyat Tsuru No Ongaeshi - Sonjaya, Ferlan (ppjbsip, 2022)
This research is motivated by the intrinsic elements contained in the folklore entitled 'The Origin of Lake Toba' with the story 'Tsuru No Ongaeshi'. The purpose of this study is to seek and find the similarities and differences of intrinsic elements between Indonesian folklore entitled 'The Origin of Lake Toba' and also Japanese folklore entitled 'Tsuru No Ongaeshi'. This study uses a genetic structural approach, where this approach is carried out by comparing and analyzing the structure of the story using the intrinsic elements in each story. The results of this study indicate that in the folklore